Perancangan Sistem Informasi Pengelolaan Barang Laboratorium Komputer Berbasis Web SMKN 1 Sintuk Toboh Gadang - Mayendri, Ollga Angelique; Mary, Thomson; Pernanda, Anggri Yulio (JURTEII: Jurnal Teknologi Informasi, 2024)
At SMKN 1 Sintuk Toboh Gadang, managing laboratory equipment was done manually or on paper, which had its disadvantages. The data was prone to tearing, getting wet, burning, or even disappearing. Therefore, a web-based laboratory item management system was designed using PHP modeling language. After beta testing and validation from experts, the system was found to have very good information with an average percentage value of 80.3%. The user assessment questionnaire also obtained an average value of 85.7% with very good information. This system is expected to prevent errors and serve as an evaluation material for the school.